PENGARUH KARAKTERISTIK PEKERJAAN, LINGKUNGAN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU SMK NEGERI 1 PRINGAPUS AMBARAWA (Students' Journal of Economic and Management, 2016)
The purposeof this studyto analyze the effectof job characteristics, work environment andorganizational culture onteacherperformance. Objectof this researchisSMNegeri1PringapusAmbarawa. The sampling techniqueusedissamplingsaturatednumbering 70respondents in the sampledata collection methodthat useskiisioner(questionnaire) by submittinga list of questionsto the respondentin order toobtaininformation. The results ofthe studyare: (1) Job Characteristicspositive and significant impacton teacher performance, (2) Work Environmentpositive and significant impacton teacher performance, and(3) CulturalOrganisationpositive and significant impacton teacher performance. Keywords: characteristics, work environment, organizational culture andperformance